Inelastic behavior of a bridge bent subjected to truck impact: Experimental and computational study. (15th November 2019) - Chen, Xi; Agrawal, Anil Kumar; El-Tawil, Sherif; Xu, Xiaochen; Cao, Ran; Wong, Waider
Highlights: A unique field experimental study is conducted to investigate the behavior of a reinforced concrete pier bent subjected to impact by a surrogate truck model. A computational model of the test setup is presented. Finite element model used to conduct parametric simulations is validated by the measured and other experimental data. The computational exercise highlighted that the current AASHTO-LRFD (2012) provisions do not adequately articulate their intent. Abstract: A unique field experimental study was conducted to investigate the behavior of a reinforced concrete pier bent subjected to impact by a surrogate truck model. The bent was a two-bay, one-story frame that represented a realistic highway structure. It was tested at half scale at the FHWA-FOIL facility. The surrogate truck model consisted of a pendulum with a specially designed impactor that was progressively crushed to represent the impact demands associated with truck collision. The bent was proportioned such that the two exterior columns had different capacities, thereby accommodating two separate tests. After validating the pre-test simulation model using the measured and other experimental data, parametric simulations were conducted to gain insight into the failure response of the bent and to critique the AASHTO truck impact guidelines. The necessity for developing performance-based design guidelines for truck-versus-pier crashes was highlighted.